PENGUATAN KAPASITAS BIDAN DAN KADER PUSKESMAS DUREN: TRAINING OF TRAINER MODEL PENDAMPINGAN DIGITAL PERAWATAN KEHAMILAN-NIFAS - Wulandari, Respati; Wibowo, Syifa Sofia; Apriyanti, Apriyanti; Fahmi, Amiq; Laurensius Tokan, Geraldinho; Yumna Huwaida, Imtiyaz (Indonesian Journal of Health Information Management Services, 2025)
The phenomenon of teenage pregnancy has serious health, social, and economic impacts. Globally, 55% of pregnancies among 15-19 year olds result in unsafe abortions, including in Indonesia. Based on interviews with the midwife coordinator, BOK funds are only sufficient to hold classes for 15 pregnant women. There is a disparity between the number of pregnant women and the amount of assistance provided so far. Of the 399 pregnant women, only 18.8% (75 women) can be assisted through classes for pregnant women. The next problem is the low reading interest of mothers in KIA books. With the availability of digital educational media, it is hoped that this can be a solution to the problems occurring at the Duren Posyandu. The purpose of this activity is to increase the knowledge of midwife cadres regarding digital education models that can accommodate more pregnant women by using educational materials that are more interesting to pregnant women. The community service activity was carried out on July 31 - August 1, 2025, with 5 village midwives and 13 cadres participating. The activity began with a pre-test, followed by the community service team delivering the material, and finally a post-test. All participants in the activity experienced an increase in knowledge for 20 points, as evidenced by their post-test scores, which were higher than their pre test scores.